Views held by Slovene coaches on some contents-related issues of their professional work - Jošt, Bojan (Kinesiologia Slovenica, 2001)
The objective of the research was to establish the structure of views on some contents-related issues concerning professional work of coaches in Slovene competition sports on a representative sample of Slovene coaches (n = 1418) from 64 sports. On the basis of the structure of the answers to individual survey questions, the following findings could be revealed. In the opinion of the major proportion of the coaches, the salaries of coaches are still too low in comparison to the high demands and scope of their work and should be regulated systemically and in the same way for all sports on the level of the state. The majority of the coaches were of the opinion that the work of coaches should even to a greater extent be based on material rewarding. The satisfaction of the coaches with their work is high; only 3% of the coaches expressed pronounced discontent with their work. The coaches still positively evaluate the relationship of the employers to their work and have the feeling that the employers esteem and respect them. The coaches were less satisfied with the material conditions in which they worked: only every fifth coach was of the opinion that material conditions for their work were good. The coaches pronounced themselves mostly in favour of the legislative regulation of their work and voiced the opinion that there should be a corresponding professional association of coaches on the state level. They also supported the project of the employment of coaches by the Ministry of Education and Sport in the future. The coaches mainly agree with the statement that their work is primarily managerial and that in the period of adolescence they perform an extremely important educational function. The majority of the coaches were of the opinion that their work is more difficult than that of the teachers of physical education in schools and at the same time socially less respected. The licensing system should include payment of the licence, suitable education, and permanent extended professional training. Only every fifth coach agreed with the statement that in his or her professional work he or she had good possibilities for research work, innovations, creativity, and own studies.
Keywords: delovni pogoji; poklicno delovanje; raziskave; Slovenija; sociologija športa; trenerji